Pengenalan Aplikasi Macromedia Flash 8 Pada SMKS Bina Satria Medan - Wulan Dari; Dian Maya Sari; Jamil Azhari Matondang (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
This introduction to the Macromedia Flash 8 application aims to provide students with understanding and skills in using Macromedia Flash 8 for design and understanding the use of Flash 8. Introduction to the Macromedia Flash 8 application is often needed in creating animations and designs for student learning. The Macromedia Flash 8 application allows its introduction to be personal and efficient, by using image and sound designs from separate sources into one Macromedia Flash 8 application. During the introduction to the Macromedia Flash 8 Application, participants will be taught about the concept of designing the use of Macromedia Flash 8, steps -design preparation steps, creating animations using Macromedia Flsah 8, and merging data into the application. This introduction to the Macromedia Flash 8 application will also discuss the benefits of using Macromedia Flash 8, including time efficiency and accuracy in the student learning that will be created. Through a combination of theory and practical exercises, participants.It is hoped that they will be able to master the steps in the application development process that will be presented using Macromedia Flash 8. The results of this training are expected to provide participants with the ability to create personal and efficient student animations, including for education and other organizations. Thus, the introduction of this application contributes to increasing the effectiveness of communication in various activities involving the student learning process.